2016
DOI: 10.1016/j.seizure.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders comorbid with epilepsy in a prison sample

Abstract: The most common psychiatric comorbid disorders among prisoners diagnosed with epilepsy were depression and anxiety as general population with epilepsy whereas some disorders, personality disorder, substance dependence and bipolar affective disorders, were found to be more common among prisoners compared to the general population with epilepsy. It is crucial to question psychiatric symptoms and comorbidities while evaluating the patients with epilepsy, especially among prisoners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…The magnitude of common mental disorders in the current study is in line with the findings done in Mexico [24] (36.4%) and in India (32.5%) [25,26]. However, this study has revealed much lower magnitude of comorbidity of common mental illness than the result done in Zambia (53.7%) [27], Brazil (54.1%) [28], India (50.0%) [29], and Turkey(40.5%) [30]. The higher prevalence in Zambia and Brazil might be because of differences in inclusion criteria and instrument variation for screening mental illness.…”
Section: Discussionsupporting
confidence: 90%
“…The magnitude of common mental disorders in the current study is in line with the findings done in Mexico [24] (36.4%) and in India (32.5%) [25,26]. However, this study has revealed much lower magnitude of comorbidity of common mental illness than the result done in Zambia (53.7%) [27], Brazil (54.1%) [28], India (50.0%) [29], and Turkey(40.5%) [30]. The higher prevalence in Zambia and Brazil might be because of differences in inclusion criteria and instrument variation for screening mental illness.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the surveys of Turkish prisoners diagnosed with epilepsy it was found, that the most common mental disorders coexisting with epilepsy was depression and anxiety disorders that occurred with the same frequency as among people from the general population with epilepsy. In contrast, personality disorders, addiction to psychoactive substances and bipolar disorder were more common among prisoners with diagnosed epilepsy [21]. The subject of our research was not the coexistence of epilepsy with other neurological diseases and mental disorders, only the frequency of occurrence, in addition to epilepsy and alcohol dependency syndrome, personality disorders, anxiety disorders and depression.…”
Section: Discussionmentioning
confidence: 99%
“…A Turkish study among prisoners with epilepsy also showed a higher prevalence of psychological distress as compared to our results (40.5%). 31 The reason for this variation might be due to the fact that there may be stressors (comorbidities, poor social support, or economic problems) in prisons which can directly provoke psychological distress.…”
Section: Discussionmentioning
confidence: 99%